UNRAVELING THE COMPLEXITY OF POLITICAL COMMUNICATION AMID THE TIDE OF DISINFORMATION AND DIGITAL POLARIZATION - Ahmad Sampurna; Nanda Risani Raqiqah; Dwi Asyila Sabrina Br. Saragih; Muammar Dzaki Ihsani; Muqtada Ibrahim; Muhammad Syarif Harefah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
Political communication serves as a crucial foundation for democratic governance, enabling governments, the media, and the public to engage in open dialogue and information exchange. In the digital era, political communication is increasingly shaped by issues such as disinformation, social media algorithms, and the dissemination of propaganda. This study adopts a qualitative approach through literature review and content analysis to explore key topics in political communication, including media framing, smear campaigns, and technical effects such as deepfakes and political influencers. Elitist political communication characterized by inefficiency, misinformation, and a lack of transparency can negatively impact public trust and escalate polarization. Adaptive communication strategies, strong problem-solving skills, and robust digital capabilities are essential to uphold democratic integrity. For political communication to be effective, transparency, integration, and interactivity are vital to fostering public participation, navigating the complexities of new media, and maintaining political stability.